Stories of Autism: What the Rise of Books on Autism Tells Us About, Well, Autism - Ryskamp, Dani Alexis (Disability Studies Quarterly, 2017)
Publications on autism have exploded in recent years, as "Autism Spectrum Disorder" becomes not only a diagnostic category, but a cultural phenomenon. In this piece, I review and analyze five major works on autism published between 2014 and 2016: In A Different Key, by John Donvan and Caryn Zucker; Autism and Gender, by Jordynn Jack; War on Autism, by Anne McGuire; Uniquely Human, by Barry Prizant; and The ABCs of Autism Acceptance, by Sparrow Rose Jones. In reviewing these works, I analyze both the points at which they merge and the points at which they diverge, and I explore the ways in which these points construct, contribute to, and/or complicate our understanding of "what autism is."